Research of material and technical resources inventory management in projects supply chains - Semenchuk, Kateryna; Shutenko, Tetiana (Technology audit and production reserves, 2021)
The object of research is the processes of material and technical support of projects in the field of supply chain management. One of the most challenging areas faced by logistics and project managers is determining the appropriate level of supply chain inventory management when implementing projects. Today, there is a demand for the development and implementation of dynamic supply chains, the essence of which is to increase the service level by increasing the speed of response to customer requests and flexibility in excess components (high stock levels, unbalanced duration of supply cycles), taking into account the uncertainty of demand.The analysis of the justification of the value of the supply chain, namely of such components as logistics costs, the cost of storing inventories and deficit costs, is carried out. Models of inventory management in the supply chain with centralized and decentralized service are presented. Calculations of the indicators of the standard deviation of demand and the duration of the supply cycle, the values of the cyclic and safety stock are presented. For the situation of centralized service of the resource flow, the influence of the demand dependence on the stock level was investigated.The study used the theory of supply chain management and project management, which made it possible to take into account the variability of demand and the duration of supply. As a result of the work, models of the volume of insurance stocks in conditions of uncertainty in demand and the duration of the supply cycle of resources are proposed. In order to ensure the optimal strategy of resource provision, the concept of «service level» was investigated. The service level of the first kind (cyclical service level) and the service level of the second kind (saturated demand) are considered.The results of this research provide an opportunity to improve project efficiency in the face of volatile demand, reduced product life cycle and increased competition. Such changes require supply chains to develop strategies that are focused on the end user, that is, an integrated supply chain management strategy is required.